2013
DOI: 10.1016/j.whi.2013.06.005
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Study of Provider Perspectives of Structural Barriers to Cervical Cancer Screening Among First Nations Women

Abstract: Objective-In Canada, opportunistic screening programs have successfully reduced mortality from cervical cancer; however, minority or disadvantaged groups, as well as women in northern and rural areas, are inadequately recruited by this approach. Hence, we set out to examine the structural barriers that prevent First Nations women's participation in cervical cancer screening.Methods-Using a participatory action research approach and semistructured interview guides, we conducted in-depth interviews with 18 exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
130
0
18

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(152 citation statements)
references
References 18 publications
4
130
0
18
Order By: Relevance
“…This study identifies many of the same barriers found in the literature that categorize Latino clinical trial retention barriers: familial relationships and issues [22], lack of transportation, employment interferences [23], economic stress [24] and financial costs [25], insufficient caregiving resources to meet demands [26], practical barriers [24,27], like interference with other top priorities of life such as work and family obligations [26], and systems barriers [28][29][30]. Andersen and Newman's [16] framework helps illuminate new and important Predisposing "Psychological Coping" Belief barriers specific to this co-morbid population, that are not specifically indicated in the literature (i.e., "feeling better;" "not interested;" "emotional stress;" grief over "loss;" untreated panic attacks; and anxiety over fertility issues).…”
Section: Discussionmentioning
confidence: 99%
“…This study identifies many of the same barriers found in the literature that categorize Latino clinical trial retention barriers: familial relationships and issues [22], lack of transportation, employment interferences [23], economic stress [24] and financial costs [25], insufficient caregiving resources to meet demands [26], practical barriers [24,27], like interference with other top priorities of life such as work and family obligations [26], and systems barriers [28][29][30]. Andersen and Newman's [16] framework helps illuminate new and important Predisposing "Psychological Coping" Belief barriers specific to this co-morbid population, that are not specifically indicated in the literature (i.e., "feeling better;" "not interested;" "emotional stress;" grief over "loss;" untreated panic attacks; and anxiety over fertility issues).…”
Section: Discussionmentioning
confidence: 99%
“…Six studies were carried out in Brazil [13,14,15,16,17,18] and four in the United States [19,20,21,22] . There was only one article from each of the following countries: Argentina [23] , Australia [24] , Canada [25] , England [26] , Italy [27] , Malawi [28] , Zambia [29] and United Kingdom [30] . Thus, the final sample comprised 18 articles.…”
Section: Characterizing the Studiesmentioning
confidence: 99%
“…components focused on preventing cervical cancer such as health education, screening, treatment and palliative care when they analyzed data related to programs, guidelines and the legislation about the topic in their country [28] . On the other hand, Maar et al (2013) (CA) identified lack of indigenous women description as special population in the country's policy [25] .…”
Section: Following-up and Monitoring The Actions Takenmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the Pap smear is the most widely used and accepted screening tool, it requires strict follow up to be effective. Patient communication, understanding, and health literacy are some of several structural barriers that are key elements of adherence to this screening test [6,7]. While studies show that educational interventions promote utilization of pap smears and adherence to testing, there is a paucity of published data regarding the efficacy of available educational material [8].…”
Section: Introductionmentioning
confidence: 99%